2016
DOI: 10.1097/jnr.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Living With Chronic Obstructive Pulmonary Disease

Abstract: Patients naturally become experts with regard to their lives through a process of trial and error. Even so, healthcare professionals play a key role in the process of self-management and help patients with COPD cope with various problems in their daily lives. The findingsof this study contribute to the development of evidence-based self-management interventions that promote quality of life in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Of the remaining articles, two by Andersen et al 29 , 30 concerned the same study and two by Chen et al also reported on one study. 31 , 32 In both instances these were analysed as one. The paper by Ogunbayo et al is from the same research team as this review.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining articles, two by Andersen et al 29 , 30 concerned the same study and two by Chen et al also reported on one study. 31 , 32 In both instances these were analysed as one. The paper by Ogunbayo et al is from the same research team as this review.…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety and depression are the major comorbidities in COPD patients (Chen, Liu, Shyu, & Yeh, 2016;Tselebis et al, 2016). Noted that COPD patients suffering from anxiety and depression are associated with an increased risk of exacerbations, hospitalisation and poorer overall health status and prognosis of COPD treatment (GOLD, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Self-management behaviours are affected by the patient's living environment and include individuals' awareness of the disease and symptom, lifestyle changes, psychosocial conditions and discussion with health professionals (Chen, Chen, Lee, Cho, & Weng, 2008;Kong et al, 2015Kong et al, , 2018. The influence of environmental factors, such as support and illness experiences from social relationships, on chronic disease self-management is as critical as that of personal factors, such as disease severity (Bhandari & Kim, 2016;Chen, Liu, Shyu, & Yeh, 2016). Findings of note are that patients with chronic hepatitis B spend most of their time on self-care at home, and therefore, disease self-management plans should be patient-centred (Cedeño-Moreno, Vargas-Lombardo, Salas-Zárate, Paredes-Valverde, & Valencia-García, 2017; Robotin & George, 2014;Yang, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%